NOX5 is expressed aberrantly but not a critical pathogenetic gene in Hirschsprung disease - Jing Wang; Jun Xiao; Xinyao Meng; Xufeng Chu; Di Di Zhuansun; Bo Xiong; Jiexiong Feng (BMC, 2021)
Abstract Background Hirschsprung disease (HSCR) is a congenital disorder characterized by the absence of intramural ganglion cells in the distal gastrointestinal tract (GI), which results in tonic contraction of the aganglionic gut segment and functional intestinal obstruction. Recent studies have suggested NADPH oxidase 5 (NOX5) as a candidate risk gene for HSCR. In this study, we examined the function of NOX5 to verify its role in the development of the enteric nervous system (ENS). Methods HSCR tissue specimens (n = 10) were collected at the time of pull-through surgery and control specimens (n = 10) were obtained at the time of colostomy closure in patients. The NOX5 expression in aganglionic and ganglionic segments of HSCR colon and normal colon were analyzed by immunohistochemistry (IHC), western blot and real-time quantitative PCR (qPCR). The gene expression levels and spatiotemporal expression spectrum of NOX5 in different development stages of zebrafish embryo were determined using qPCR and in-situ hybridization (ISH). The enteric nervous system in NOX5 Morpholino (MO) knockdown and wild type (WT) zebrafish embryo was analyzed by whole-mount immunofluorescence (IF). Intestinal transit assay was performed to analyze the gastrointestinal motility in NOX5 knockdown and control larvae. Results NOX5 is strongly expressed in the ganglion cells in the proximal segment of HSCR colons and all segments of normal colons. Moreover, the expression of NOX5 is markedly decreased in the aganglionic segment of HSCR colon compared to the ganglionic segment. In zebrafish, NOX5 mRNA level is the highest in the one cell stage embryos and it is decreased overtime with the development of the embryos. Interestingly, the expression of NOX5 appears to be enriched in the nervous system. However, the number of neurons in the GI tract and the GI motility were not affected upon NOX5 knockdown. Conclusions Our study shows that NOX5 markedly decreased in the aganglionic segment of HSCR but didn't involve in the ENS development of zebrafish. It implies that absence of intestinal ganglion cells may lead to down-regulation of NOX5.